Prediction of biochemical mechanism of anti-inflammation explained from two marine-derived bioactive compounds - Sornsiri, Jidapa; Srisook, Klaokwan; Pornngam, Preedawan; Sootanan, Pitak (Agriculture and Natural Resources, 2018)
Marine brown macroalgae contain several bioactive compounds with potent anti-inflammatory properties but undescribed pharmacological properties. This study provided the first description of the biochemical mechanism of anti-inflammation from two bioactive compounds (fucoxanthin and sargachromenol) found in brown macroalgae (Sargassum spp.) based on a functional module-based analysis of a protein-protein interaction (PPI) network. The constructed PPI network of fucoxanthin and sargachromenol with 18 and 5 inflammatory proteins, respectively, have scale-free, small world and modular properties. There were 6 and 1 inflammatory modules found associated with the antiinflammatory actions of fucoxanthin and sargachromenol, respectively. Of particular interest was that the anti-inflammatory effect of fucoxanthin and sargachromenol may be partly attributable to regulation of the I-kappa B kinase/NF-kappa B cascade and regulation of gene expression, respectively. These can be used to search for potential targets of fucoxanthin and of sargachromenol to treat inflammation. Therefore, functional module-based analysis of a PPI network can be an initial method for elucidating the anti-inflammatory mechanism of active compounds and finding their targets to validate in a wet laboratory clinical application and for further drug development.